Diffuse Multifocal Bilateral Dysembryoplastic Neuroepithelial Tumor: A Very Unusual Case Report - Mohammadi, Hassan Reza; Moradi, Ehsan; Rahimian, Elham; Varlet, Pascal; Nilipor, Yalda (International Clinical Neuroscience Journal, 2020)
Dysembryoplastic neuroepithelial tumor (DNT) considered as a benign cortical Glioneuronal neoplasm of children or young adults, typically present with drug-resistant focal epilepsy. DNTs are usually located in the temporal lobe but can found in any part of the supratentorial brain cortex. Multifocal DNTs have rarely reported. Here we present an eight years old boy with two years follow up, having a somewhat stable diffuse multinodular DNT of the most significant spatial extent that may have reported, involving cortical and subcortical left temporo-occipital lobe, bilateral basal ganglia and thalamus, presenting with headache, short stature, and behavioral disorder.